Obesity is a risk factor for central precocious puberty: a case-control study - Liu, Gaiyan; Guo, Jinxin; Zhang, Xuejing; Lu, Yu; Miao, Junjie; Xue, Hongmei (BMC pediatrics, 2021)
Obesity is an important underlying cause of central precocious puberty (CPP), but previous large studies are flawed by using just age and breast examination to diagnose CPP. We aimed to determine whether overweight and obesity in childhood increases hormonally diagnosed CPP. Our retrospective, case-control study recruited 846 children diagnosed as having CPP and randomly sampled 1650 healthy control subjects in Xingtai Third Hospital in China between November 2018 and March 2021. Information was obtained from an electronic medical record and questionnaire investigated in the outpatient visit. Observations were made before the a priori hypothesis. Unconditional logistic regression for analysis was used to determine whether overweight and obesity status and duration of overweight/obesity were associated with CPP. Overweight and obesity were significantly associated with increased odds of CPP among girls, even after adjusting for birth weight, exclusive breastfeeding for 6 month, household income, maternal overweight, paternal overweight, and maternal menarche age (overweight: the adjusted odds ratio (aOR) (95%CI): 1.92 (1.16, 3.24), p = 0.02; obesity: aOR (95%CI): 1.78 (1.13, 3.48), p = 0.03). Furthermore, the effects of overweight and obesity were significant when ongoing for 1 to 2 years, 2 to 3 years, and greater than 3 years, but not at less than 1 year. For boys, association between obesity and increased odds of CPP was observed (aOR (95%CI): 1.68 (1.09, 3.75), p = 0.03). The effects of overweight and/or obesity were only significant when ongoing for greater than 2 years. Prolonged overweight and obesity in early childhood may be risk factors for CPP, especially in girls. Weight loss might be an important approach for the prevention of precocious puberty in children.